SnO2 Nanofibers Network for Cold Cathode Applications in Vacuum Nanoelectronics. (19th June 2022) - Giubileo, Filippo; Faella, Enver; Pelella, Aniello; Kumar, Arun; Capista, Daniele; Passacantando, Maurizio; Kim, Sang Sub; Di Bartolomeo, Antonio
Abstract: Field‐emission cold cathodes are the key components of vacuum nanoelectronics that offer great advantages over other electron sources based on the thermionic or photoelectric effects. In the effort to realize new electron sources, a systematic investigation of the field emission (FE) properties of SnO2 nanofiber networks is performed. High‐purity SnO2 nanofibers, confirmed by X‐ray photoelectron spectroscopy, are prepared by electrospinning technique and then uniformly distributed over Si wafer. Field emission properties are investigated using a nanomanipulated tip‐shaped anode, inside a scanning electron microscope, for fine tuning the anode‐cathode separation distance. A field‐emission current is observed with an applied electric field as low as 25 V μ m −1 . Performance parameters such as turn‐on field and field enhancement factor are evaluated within the theoretical Fowler–Nordheim framework as a function of the anode–cathode separation distance, demonstrating that a maximum enhancement factor of about 150 is obtained at a separation of 200 nm. The emission from a single nanofiber is characterized by a current saturation at high voltages that can be explained in terms of electron supply limitation within conduction band. No evidence of field emission current contribution by electron tunneling from the valence band is observed in the experimental data. Abstract : The field emission properties of electrospinned SnO2 nanofibers are investigated by tip‐anode experimental setup for local characterization. It is demonstrated that for a cathode–anode separation below 1 µm the field enhancement factor increases for reducing distances while the turn‐on field necessary to switch‐on the current decreases. Current saturation regime is observed for individual nanofiber.